Transcriptome analysis of the pulp of citrus fruitlets suggests that domestication enhanced growth processes and reduced chemical defenses increasing palatability - Perez-Roman, Estela; Borredá, Carles; Tadeo, Francisco R.; Talon, Manuel (Frontiers in Plant Science, 2022)
To identify key traits brought about by citrus domestication, we have analyzed the transcriptomes of the pulp of developing fruitlets of inedible wild Ichang papeda (C. ichangensis), acidic Sun Chu Sha Kat mandarin (C. reticulata) and three palatable segregants of a cross between commercial Clementine (C. x clementina) and W. Murcott (C. x reticulata) mandarins, two pummelo/mandarin admixtures of worldwide distribution. RNA-seq comparison between the wild citrus and the ancestral sour mandarin identified 7267 differentially expressed genes, out of which 2342 were mapped to 117 KEGG pathways. From the remaining genes, a set of 2832 genes was functionally annotated and grouped into 45 user-defined categories. The data suggest that domestication promoted fundamental growth processes to the detriment of the production of chemical defenses, namely, alkaloids, terpenoids, phenylpropanoids, flavonoids, glucosinolates and cyanogenic glucosides. In the papeda, the generation of energy to support a more active secondary metabolism appears to be dependent upon upregulation of glycolysis, fatty acid degradation, Calvin cycle, oxidative phosphorylation, and ATP-citrate lyase and GABA pathways. In the acidic mandarin, downregulation of cytosolic citrate degradation was concomitant with vacuolar citrate accumulation. These changes affected nitrogen and carbon allocation in both species leading to major differences in organoleptic properties since the reduction of unpleasant secondary metabolites increases palatability while acidity reduces acceptability. The comparison between the segregants and the acidic mandarin identified 357 transcripts characterized by the occurrence in the three segregants of additional downregulation of secondary metabolites and basic structural cell wall components. The segregants also showed upregulation of genes involved in the synthesis of methyl anthranilate and furaneol, key substances of pleasant fruity aroma and flavor, and of sugar transporters relevant for sugar accumulation. Transcriptome and PCR analysis in developing and ripe fruit of a set of genes previously associated with citric acid accumulation, demonstrated that lower acidity is linked to downregulation of these regulatory genes in the segregants. The results suggest that the transition of inedible papeda to sour mandarin implicated drastic gene expression reprograming of pivotal pathways of the primary and secondary metabolism, while palatable mandarins evolved through progressive refining of palatability properties, especially acidity.